Reference without referents - Sainsbury, R. M. (Richard Mark); Oxford University Press (Oxford ; New York : Clarendon Press, 2005)
Reference is a central topic in philosophy of language. This book sets out a new approach to the concept, which promises to bring to an end some long-standing debates in semantic theory. It also includes an historical survey. It will be of interest to those working in logic, mind, and metaphysics.
A short history of theories of names -- Framework issues -- Proper names -- Pronouns : anaphora and demonstration -- Complex referring expressions -- Existence and fiction -- Mental reference and individual concepts.
Includes bibliographical references (pages 255-260) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Reference (Philosophy); Language and languages -- Philosophy; Référence (Philosophie); Langage et langues -- Philosophie; PHILOSOPHY -- Epistemology; Language and languages -- Philosophy; Reference (Philosophy)